Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1109/tnsre.2021.3107376
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of a Postural Synergy-Based Exoskeleton for Post-Stroke Upper Limb Rehabilitation

Abstract: Upper limb exoskeletons have drawn significant attention in neurorehabilitation because of the anthropomorphic mechanical structure analogous to human anatomy. Whereas, the training movements are typically unorganized because most exoskeletons ignore the natural movement characteristic of human upper limbs, particularly inter-joint postural synergy. This paper introduces a newly developed exoskeleton (Armule) for upper limb rehabilitation with a postural synergy design concept, which can reproduce activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 57 publications
(71 reference statements)
0
17
0
Order By: Relevance
“…The English national quality standard states that stroke patients must be given a minimum of 45 min of each necessary therapy, at least 5 days a week. The vast majority of rehabilitation strategies for exoskeleton follow this standard, such as He et al ( 2021 ), the participants underwent task-specific training involving 5-DoFs upper extremity movements in a three-dimensional environment with the aid of an exoskeleton for 45 min per day, 5 days per week, for 4 weeks (total of 20 sessions). In every session, the participants were required to complete two sets of exercises.…”
Section: Challenges In Upper-limb Exoskeleton Developmentmentioning
confidence: 99%
“…The English national quality standard states that stroke patients must be given a minimum of 45 min of each necessary therapy, at least 5 days a week. The vast majority of rehabilitation strategies for exoskeleton follow this standard, such as He et al ( 2021 ), the participants underwent task-specific training involving 5-DoFs upper extremity movements in a three-dimensional environment with the aid of an exoskeleton for 45 min per day, 5 days per week, for 4 weeks (total of 20 sessions). In every session, the participants were required to complete two sets of exercises.…”
Section: Challenges In Upper-limb Exoskeleton Developmentmentioning
confidence: 99%
“…Spinal cord injury (SCI) and stroke are two major neurological diseases that cause motor disorders of the upper and lower extremities, and the mobility of limbs varies according to the degree of injuries. Although some muscles may still function in some ways, this does not necessarily mean that they have direct control over the limb, which can limit activities of daily living (ADL) [1,2]. Extremity disability will severely affect the autonomy and quality of life as well as burden families and society [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although some muscles may still function in some ways, this does not necessarily mean that they have direct control over the limb, which can limit activities of daily living (ADL) [1,2]. Extremity disability will severely affect the autonomy and quality of life as well as burden families and society [2]. It has been demonstrated that beginning inpatient rehabilitation interventions as soon as the injury occurs will make them more conducive to comprehensive functional recovery [1].…”
Section: Introductionmentioning
confidence: 99%
“…S TROKE is one of the leading causes of death and disability, with approximately 42.4 million cases occurring worldwide each year [1]. One common clinical manifestation of stroke survivors is hemiplegia [2], which greatly affects their performance in activities of daily living (ADLs) and brings a heavy burden to their families [3]. Post-stroke rehabilitation is an effective way to improve the ADLs performance [4].…”
Section: Introductionmentioning
confidence: 99%